Effect of natural fermentation on the structure and physicochemical properties of wheat starch. (15th August 2019) - Zhao, Tong; Li, Xiaoping; Zhu, Ruizhen; Ma, Zhen; Liu, Liu; Wang, Xiaolong; Hu, Xinzhong
Highlights: Natural fermentation is an effective method to modify wheat starch. Wheat starch granule surface was slightly eroded during natural fermentation. The relative crystallinity of wheat starch increased after fermentation. Fermentation decreased the amorphous region of wheat starch granules. Pasting properties of wheat starch were changed by natural fermentation. Abstract: In this study, the effects of natural fermentation on the multi-scale structure and physicochemical properties of wheat starch were investigated. The results showed that fermentation reduced weight-average molecular weight ( Mw ) and slightly eroded the starch granule surface. An obvious increase in relative crystallinity from X-ray diffraction was observed in all fermented starch (39.38–42.27%) when compared with native starch (37.15%). Data from small angle X-ray scattering revealed that fermentation increased the crystalline layer and decreased the amorphous region of the starch granules. The intensity of absorption related to hydrogen bonding by FT-IR (3000–3600 cm −1 ) also increased in fermented starch. The rapid viscosity analysis results showed that fermented starch had a lower peak viscosity and final viscosity, and a lower setback value than native starch. The present results reveal that fermentation is an effective method to modify wheat starch and suggest its potential to improve the quality of starch-based foods.